Students’ Perceptions of Flipped Approach in EFL Classroom: A Survey Research - Eka Duriyatul Muhlisoh; Asih Santihastuti; Eka Wahjuningsih (JETL (Journal of Education, Teaching and Learning), 2020)
This research investigated the implementation of Flipped Approach in EFL classroom with the implementation of the E-learning platform. The participants were 42 sophomore English majors of Advanced Paragraph Writing class at Jember University. A within-subjects research design exposed all participants to have Writing Class by flipped learning and to use the E-learning platform. A one-shot survey design was used in this research by distributing two questionnaires “Perception of Flipped Learning Experience” and “Technology Acceptance Model” and doing the in-class observations as “Flipped Note” to collect the data. Data were analyzed quantitatively through SPSS 16.0 by applying the formula of Descriptive Statistics. The results of this research revealed that the implementation of the flipped approach in the classroom: (1) motivated the students in learning the materials, (2) enhanced the students’ knowledge, (3) and engaged them more in the learning tasks. They explained that the flipped approach gave them a new experience in language learning processes, in which they learned the materials before coming to the classroom so that they could criticize the materials. This way of learning aligns with the idea of student-centred learning. It is notable, however, that the students who did not learn the materials yet, could not criticize the materials and could not reach better outcomes in flipped classroom Moreover, the use of E-learning in the flipped classroom gave the students beneficial outcomes in the learning processes. Students revealed on the Technology Acceptance Model questionnaire that E-learning facilitates them properly, and they wanted to look forward to having E-learning in the future learning processes. Despite this finding, there remain limitation on the “server down” issue which needs to be straightened for more accessible E-learning among users.